2014
DOI: 10.2495/eq140892
|View full text |Cite
|
Sign up to set email alerts
|

Energy from municipal solid waste

Abstract: This paper presents an overview of the solutions available for obtaining energy from municipal solid waste. Special waste is not taken into account because of its extreme variability of characteristics from region to region and from type to type. On the contrary, municipal solid waste shows aspects useful for a more homogeneous analysis of international interest concerning the exploitation of its energy content. The first part of this paper deals with the evolution of the interest towards energy recovery from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 24 publications
0
23
0
2
Order By: Relevance
“…Several types of material, such as paper, glass, and plastic could be transformed into other usable products. In addition, energy recovery from waste is also proposed, since it was found that waste could be used to generate fuel and energy through a different waste process [17][18][19][20][21][22]. However, some types of waste, particularly hazardous waste, are not easy to reuse and recycle.…”
Section: Introductionmentioning
confidence: 99%
“…Several types of material, such as paper, glass, and plastic could be transformed into other usable products. In addition, energy recovery from waste is also proposed, since it was found that waste could be used to generate fuel and energy through a different waste process [17][18][19][20][21][22]. However, some types of waste, particularly hazardous waste, are not easy to reuse and recycle.…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, there are different types of technologies for the same thermal treatment processes [19][20][21][22][23][24][25][26]. Source reduction, generation, recovery and disposal [27,28] constitute some of the most important segments of integrated MSW management (IMSWM).…”
mentioning
confidence: 99%
“…This fraction is partially biodegradable, so it is not considered as pure biomass. However, MSW refuse usually contains a biodegradable fraction over 50% [13] and therefore, it could be interesting use it as feedstock for bioenergy production [14]- [16]. The studied concept of advanced WtE plant is a facility producing products and/or services from MSW refuse e.g.…”
Section: The Role Of Msw Refuse In Bioenergymentioning
confidence: 99%